2020
DOI: 10.37962/jpps.v8i2.368
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Anxiolytic and Antidepressant of Methanolic Leaves Extract of Syzygium Cumini in Mice

Abstract: Background: Anxiety and depression are very common in clinical practice and reduce the overall quality of life. In recent years, various researchers have focused on natural products which are derived from medicinal plants. Studies suggested that diet rich in flavonoids, vitamins and antioxidants are the important components in reduction of anxiety and depression. Objective: Hence current investigation was aimed to assess the anxiolytic and antidepressant effects of Syzygium cumini in mice at 125, 250 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Table S6 and S7 families, there are two plants with the potential to overcome health disorders, namely Syzygium aromaticum and Syzygium cumini (Myrtaceae), as well as Piper methysticum L. and Piper nigrum Linn. (Piperaceae) (Rehman et al, 2020;P. Tiwari et al, 2014;Emon et al, 2021).…”
Section: Scientific Evidence Indonesian Medicinal Plants Overcome Men...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Table S6 and S7 families, there are two plants with the potential to overcome health disorders, namely Syzygium aromaticum and Syzygium cumini (Myrtaceae), as well as Piper methysticum L. and Piper nigrum Linn. (Piperaceae) (Rehman et al, 2020;P. Tiwari et al, 2014;Emon et al, 2021).…”
Section: Scientific Evidence Indonesian Medicinal Plants Overcome Men...mentioning
confidence: 99%
“…Tiwari et al, 2014;Emon et al, 2021). S. aromaticum has antianxiety activity, while S. cumini possesses antidepressant, antianxiety, and sedative effects (Galal and Abdellatief 2015;Rehman et al 2020). P. nigrum Linn.…”
Section: Scientific Evidence Indonesian Medicinal Plants Overcome Men...mentioning
confidence: 99%
“…intrinsic renal azotemia, prerenal azotemia and postrenal azotemia [2]. Recently, many studies reported the significant pharmacological activities of different plant extracts [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%